Diagnostic value of circulating microRNAs compared to high-sensitivity troponin T for the detection of non-ST-segment elevation myocardial infarction. (14th October 2021) - Biener, M; Giannitsis, E G; Thum, T; Baer, C; Costa, A; Andrzejewski, T; Stoyanov, K M; Vafaie, M; Meder, B; Katus, H A; De Gonzalo Calvo, D; Mueller-Hennessen, M
Abstract: Background/Introduction: MicroRNAs (miRNAs) are promising biomarkers due to their high specificity and may facilitate differential diagnosis of patients presenting with suspected acute coronary syndrome (ACS) to the emergency department (ED). Purpose: To assess the diagnostic value of eleven miRNAs for the detection of non-ST-segment elevation myocardial infarction (NSTEMI). Methods: 1, 042 patients presenting between August 2014 and April 2017 to the ED with suspected ACS were included. NSTEMI was diagnosed per criteria of the 4th Universal definition of myocardial infarction (UDMI) using high-sensitivity troponin T (hs-cTnT). Expression levels of eleven microRNAs (miR-21, miR-22, miR-29a, miR-92a, miR-122, miR-126, miR-132, miR-133, miR-134, miR-191, miR-423) were determined using RT-qPCR. Discrimination of NSTEMI was assessed for individual and a panel of miRNAs compared to the hs-cTnT reference using C-statistics and reclassification analysis. Results: NSTEMI was diagnosed in 137 (13.1%) patients. The AUC of the hs-cTnT based reference was 0.937. In a multivariate model three miRNAs (miR-122, miR-133 and miR-134) were found to be associated with NSTEMI with AUCs between 0.506 and 0.656. A panel consisting of these miRNAs revealed an AUC of 0.662 for the diagnosis of NSTEMI. The AUC of the combination of the miRNA panel and troponin reference was significantly lower than the reference standard (AUC: 0.897 vs. 0.937, p=0.006). Despite a significant improvement of NSTEMI reclassification measured by IDI and NRI, miRNAs did not improve specificity of hs-cTnT kinetic changes for the diagnosis of NSTEMI (ΔAUC: 0.04). Conclusion: Although single miRNAs are significantly associated with the diagnosis of NSTEMI a miRNA panel does not add diagnostic accuracy to the hs-cTnT reference considering baseline values and kinetic changes as recommended by 4th version of UDMI. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): German Heart Foundation/German Foundation of Heart Research.CIBERES (CB07/06/2008 to DdGC) is a project from Carlos III Health Institute.